The dawn of everything a new history of humanity - Graeber, David 1961-2020; Wengrow, David 1972- (Farrar, Straus and Giroux, 2021)
Farewell to humanity's childhood, Or, why this is not a book about the origins of inequality -- Wicked liberty: The indigenous critique and the myth of progress -- Unfreezing the Ice Age: In and out of chains: the protean possibilities of human politics -- Free people, the origin of cultures, and the advent of private property (not necessarily in that order) -- Many seasons ago: Why Canadian foragers kept slaves and their Californian neighbours didn't; or, the problem with 'modes of production' -- Gardens of Adonis: The revolution that never happened: how Neolithic peoples avoided agriculture -- The ecology of freedom: How farming first hopped, stumbled and bluffed its way around the world -- Imaginary cities: Eurasia's first urbanites - in Mesopotamia, the Indus Valley, Ukraine and China - and how they built cities without kings -- Hiding in plain sight: The indigenous origins of public housing and democracy in the Americas -- Why the state has no origin: The humble beginnings of sovereignty, bureaucracy, and politics -- Full circle: On the historical foundations of the indigenous critique -- Conclusion: The dawn of everything
Literaturverzeichnis Seite 611-673
Keywords: Geschichte; Zivilisation; Civilization / Philosophy; Social history; World history